Reforming the Notions of Educational Innovation: A Crucial Requirement for Society (International Journal of Food and Nutritional Sciences, 2022)
India as a nation was once referred to as a golden bird due to its rich cultural heritage and resources. One of the main reasons behind this achievement was the world-class education system developed over the centuries. In recent times due to centuries of suppression, this heritage has been lost. Now Indian society is recognized in various negative issues such as underdevelopment, poverty, overpopulation, environmental issues, communal tensions, and various separatist movements. Faced with such difficulties it has been trying to regain its lost glory. Like other societies and countries, it has its aspirations and goals which can only be achieved through education. Education is the most important tool for effectively realizing those aspirations. Our society has countered these challenges by using various forms of education such as mass education, scientific and technical education, population education, environmental education, and religious education. To strengthen the education system there is a need to bring innovation in thoughts so that the country's tolerance and national unity can be maintained. There is no doubt that education provides significant assistance to the society or nation in fulfilling its aspirations and goals. Over the years many commissions, committees, and acts have been created to meet the needs and requirements of the present, which change education from time to time and provide a new direction to the society. It plays a vital role in innovation, growth, expansion, and increasing productivity in the country and nation. In the presented paper, we will discuss why there is a need to bring innovation into the thoughts of every person for the upliftment of society, and how we can take society on the path of progress and development through education